2018
DOI: 10.1093/pubmed/fdy133
|View full text |Cite
|
Sign up to set email alerts
|

Trends in social inequality in loneliness among adolescents 1991–2014

Abstract: The prevalence of loneliness increased from 1991 to 2014. The social inequality in loneliness decreased in both absolute and relative terms because of a rising prevalence of loneliness among children from high OSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 42 publications
(59 reference statements)
7
70
0
11
Order By: Relevance
“…The findings highlight the pivotal role of a lack of strong connection (parental, peer, and teacher support) as a risk to young people's mental well-being [20,21] as well as the potentially negative impact of SMU [16]. These findings are of concern in light of studies showing an increase in young people's feelings of loneliness [51] and studies highlighting the changing nature of young people's social relationships (e.g., more online [1]). Overall, results show the importance of contemporary risk factors in understanding young people's mental well-being.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The findings highlight the pivotal role of a lack of strong connection (parental, peer, and teacher support) as a risk to young people's mental well-being [20,21] as well as the potentially negative impact of SMU [16]. These findings are of concern in light of studies showing an increase in young people's feelings of loneliness [51] and studies highlighting the changing nature of young people's social relationships (e.g., more online [1]). Overall, results show the importance of contemporary risk factors in understanding young people's mental well-being.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, some of the correlations may have been significant, although small, because of the large sample size. Policy recommendations from the results include the need to assess multiple risks and to target the most salient risks for mental wellbeing, which include contemporary risks, such as problematic SMU [58] as well as lack of social support [20,51]. In conclusion, the results highlight the importance of contemporary clusters of risk, such as low social support and SMU in the mental well-being of young people and the need to focus on these as targets for prevention.…”
Section: Discussionmentioning
confidence: 91%
“…We also argue that future intervention work would do well to look at society-level variables that have been shown to influence loneliness among youth. For example, parents' low socioeconomic status has been shown to be associated with loneliness among youth (Madsen et al, 2019); parent-reported loneliness (Junttila & Vauras, 2009) is also an important predictor of youth loneliness. Neither have been used to target youth for intervention, but could prove important for prevention and intervention work.…”
Section: Modifying Riskmentioning
confidence: 99%
“…The prevalence of loneliness in the adolescent population is increasing (Madsen et al, 2019) and several studies report associations with other psychological measures, in particular depressive symptoms (Cacioppo et al, 2010). Symptoms of loneliness was measured by asking the adolescents to rate, on a four-point scale ranging from "Not at all" (1) to "Very much" (4), whether they had "Felt lonely" during the last week.…”
Section: Lonelinessmentioning
confidence: 99%